Aluminum-Alumina Composite Manufacturing: Unlocking Potential with Friction Stir Processing - Q Mohammad; K Gopal; E Poornima; Singh Navdeep; Arora Sethi Vandana; Kumari Vandna (E3S Web of Conferences, 2024)
This study investigates the manufacturing of Aluminum-Alumina composites through Friction Stir Processing (FSP) and explores the resultant enhancements in mechanical properties. A key focus lies on achieving a uniform distribution of Al2O3 particles within the composite matrix, crucial for optimizing material performance. These dispersed particles act as effective strengthening agents, impeding dislocation movement and grain boundary migration, consequently improving mechanical attributes such as hardness, strength, and wear resistance. Experimental findings underscore the efficacy of FSP in enhancing various mechanical properties of the composite. Notably, significant improvements were observed, including a 23.56% increase in tensile strength, a 37.9% enhancement in hardness, a 25.5% improvement in fatigue strength, and a notable 30.12% increase in wear resistance. These results underscore the potential of Aluminum-Alumina composites manufactured via FSP to unlock new opportunities for high-performance materials in industries requiring superior mechanical properties and wear resistance, such as aerospace, automotive, and manufacturing sectors.